Reduction of economic efficiency of marine diesel from pollution of elements and turbocharger cavity when using fuels of different composition - V. R. Vedruchenko; A. V. Shtib; I. I. Malakhov (Омский научный вестник)
The detailed analysis of pollution of details and cavities of a gas turbocharger (GTN) of a ship diesel engine is done. The composition of contaminants and their impact on the operating conditions of the diesel engine is revealed, and an approximate assessment of the economic damage from contamination of parts of the GTN cavities is carried out.